Prophetic Authority and Intellectual Humility: Revisiting the Palm Pollination Hadith in Contemporary Islamic Epistemology - Mohd Arif Nazri; Nurul Jannah Zainan Nazri; Nurul Mukminah Zainan Nazri (Nun Gemilang ENT, 2026)
Indexed by MyCite (Tier 3)